On specialized oversights: biomedicine as an intrinsic part of life for indigenous peoples - Eduardo L. Menéndez (Salud Colectiva, 2023)
The vast majority of studies on traditional medicine disregard the existence of biomedicine and alternative and complementary medicines in the lives of the indigenous peoples of Mexico and Latin America in general, despite the fact that these populations increasingly make use of biomedical knowledge more and more intensively. In this text I have attempted to elucidate this expansion of biomedicine and the decline of traditional medicine, through ethnographic information related to different indigenous groups. This expansion of biomedicine takes place despite the various negative consequences it generates due to different factors such as its comparative effectiveness, which is evidenced in the use of and demand for pharmaceuticals, biomedical services, and in particular the construction of hospitals in their communities. The indigenous population combines the uses of traditional medicine and biomedicine with a tendency to increasingly utilize biomedicine, even on the part of traditional healers.